A companion to Josephus in his world - Chapman, Honora Howell; Rodgers, Zuleika (Chichester, West Sussex, UK ; Malden, MA : John Wiley & Sons, Inc., 2016)
'Considered the most important historian of Jewish antiquity, the works of Flavius Josephus offer unparalleled insights into the world of Late Second Temple Judaism, the dawn of Christianity, and the early years of the Roman Empire. A Companion to Josephus presents a collection of readings that probe deeply into aspects relating to the four extant works of the first century Jewish historian Flavius Josephus. Featuring contributions from more than two dozen renowned international scholars specializing in Josephus and related studies, readings introduce the writings of Josephus, put them into historical contexts, explore their transmission and reception, and highlight contemporary scholarly approaches to two millennia of Josephan studies. Following an examination of the four individual texts and their manuscript tradition and situating the writings of Josephus among contemporaneous Greek, Roman, Jewish, and Christian works, a wide variety of themes are explored--the archaeology of Galilee, military history, the Jerusalem Temple, women, Jewish rulers, and more. Further readings follow the transmission and reception of the Josephan corpus along its remarkable journey from Late Antiquity through to the Medieval, early Modern, and Modern periods. In the first single-volume scholarly guide to Josephus, A Companion to Josephus sheds important new light into the writings of an eyewitness to a pivotal point in world history'--
Machine generated contents note: Notes on Contributors List of Illustrations Abbreviations Introduction I Writings 1. Judean War 2. Jewish Antiquities 3. Life 4. Against Apion II Josephus's Literary Context 5. Josephus as a Roman Historian 6. Josephus and Greek Imperial Literature 7. Josephus and the Hebrew Scriptures 8. Josephus and Philo 9. Josephus and the New Testament III Themes 10. Josephus and the Archaeology of Galilee 11. Josephus as Military Historian 12. Women in Josephus 13. The Hasmoneans in Josephus 14. Herod the Great in Josephus 15. The Herodian Temple in Josephus 16. Josephus and the Jewish Sects 17. Josephus and the Priesthood 18. Josephus and Halacha 19. Josephus and Rabbinic Literature IV Transmission And Reception History 20. The Manuscript Tradition 21. The Ancient Latin Translations of Josephus 22. The Testimonium Flavianum 23. Josephus and Patristic Literature 24. The Christian Reception of Josephus in Late Antiquity and the Middle Ages 25. Sefer Yosippon 26. The Slavonic Version of Josephus's Jewish War 27. Josephus in Renaissance Italy 28. English Translations of Josephus 29. Josephus in Hebrew Scholarship 30. Josephus Comicus in Monty Python's Life of Brian and History of the World, Part 1 .
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Josephus, Flavius; Josephus, Flavius; 586 B.C.-210 A.D; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.; Judaism -- Post-exilic period (Judaism); HISTORY / Ancient / General; History; Electronic books